Influence of soundtrack on eye movements during video exploration - Antoine Coutrot; Nathalie Guyader; Gelu Ionescu; Alice Caplier (Bern Open Publishing, 2012)
Models of visual attention rely on visual features such as orientation, intensity or motion to predict which regions of complex scenes attract the gaze of observers. So far, sound has never been considered as a possible feature that might influence eye movements. Here, we evaluate the impact of non-spatial sound on the eye movements of observers watching videos. We recorded eye movements of 40 participants watching assorted videos with and without their related soundtracks. We found that sound impacts on eye position, fixation duration and saccade amplitude. The effect of sound is not constant across time but becomes significant around one second after the beginning of video shots.